6ca6d6867cee1806f63a9f73f42957485d10a8a6
[lambda.git] / week4.mdwn
1 [[!toc]]
2
3 #These notes return to the topic of fixed point combiantors for one
4  more return to the topic of fixed point combinators#
5
6 Q: How do you know that every term in the untyped lambda calculus has
7 a fixed point?
8
9 A: That's easy: let `T` be an arbitrary term in the lambda calculus.  If
10 `T` has a fixed point, then there exists some `X` such that `X <~~>
11 TX` (that's what it means to *have* a fixed point).
12
13    let W = \x.T(xx) in
14    let X = WW in
15    X = WW = (\x.T(xx))W = T(WW) = TX
16
17 Q: How do you know that for any term T, YT is a fixed point of T?
18
19 A: Note that in the proof given in the previous answer, we chose `T`
20 and then set `X = WW = (\x.T(xx))(\x.T(xx))`.  If we abstract over
21 `T`, we get the Y combinator, `\T.(\x.T(xx))(\x.T(xx))`.  No matter
22 what argument `T` we feed Y, it returns some `X` that is a fixed point
23 of `T`, by the reasoning in the previous answer.
24
25 Q: So if every term has a fixed point, even Y has fixed point.
26
27 A: Right:
28
29     let Y = \T.(\x.T(xx))(\x.T(xx)) in
30     Y Y = \T.(\x.T(xx))(\x.T(xx)) Y
31         = (\x.Y(xx))(\x.Y(xx))
32         = Y((\x.Y(xx))(\x.Y(xx)))
33         = Y(Y((\x.Y(xx))(\x.Y(xx))))
34         = Y(Y(Y(...(Y(YY))...)))
35
36 Q: Ouch!  Stop hurting my brain.
37
38 A: Let's come at it from the direction of arithmetic.  Recall that we
39 claimed that even `succ`---the function that added one to any
40 number---had a fixed point.  How could there be an X such that X = X+1?
41 Then
42
43     X = succ X = succ (succ X) = succ (succ (succ (X))) = succ (... (succ X)...)
44
45 In other words, the fixed point of `succ` is a term that is its own
46 successor.  Let's just check that `X = succ X`:
47
48     let succ = \n s z. s (n s z) in
49     let X = (\x.succ(xx))(\x.succ(xx)) in
50     succ X 
51       = succ ((\x.succ(xx))(\x.succ(xx))) 
52       = succ (succ ((\x.succ(xx))(\x.succ(xx))))
53       = succ (succ X)
54
55 You should see the close similarity with YY here.
56
57 Q. So `Y` applied to `succ` returns infinity!
58
59 A. Yes!  Let's see why it makes sense to think of `Y succ` as a Church
60 numeral:
61
62       [same definitions]
63       succ X
64       = (\n s z. s (n s z)) X 
65       = \s z. s (X s z)
66       = succ (\s z. s (X s z)) ; using fixed-point reasoning
67       = \s z. s ([succ (\s z. s (X s z))] s z)
68       = \s z. s ([\s z. s ([succ (\s z. s (X s z))] s z)] s z)
69       = \s z. s (s (succ (\s z. s (X s z))))
70
71 So `succ X` looks like a numeral: it takes two arguments, `s` and `z`,
72 and returns a sequence of nested applications of `s`...
73
74 You should be able to prove that `add 2 (Y succ) <~~> Y succ`,
75 likewise for `mult`, `minus`, `pow`.  What happens if we try `minus (Y
76 succ)(Y succ)`?  What would you expect infinity minus infinity to be?
77 (Hint: choose your evaluation strategy so that you add two `s`s to the
78 first number for every `s` that you add to the second number.)
79
80 This is amazing, by the way: we're proving things about a term that
81 represents arithmetic infinity.  It's important to bear in mind the
82 simplest term in question is not infinite:
83
84      Y succ = (\f.(\x.f(xx))(\x.f(xx)))(\n s z. s (n s z))
85
86 The way that infinity enters into the picture is that this term has
87 no normal form: no matter how many times we perform beta reduction,
88 there will always be an opportunity for more beta reduction.  (Lather,
89 rinse, repeat!)
90
91 Q. That reminds me, what about [[evaluation order]]?
92
93 A. For a recursive function that has a well-behaved base case, such as
94 the factorial function, evaluation order is crucial.  In the following
95 computation, we will arrive at a normal form.  Watch for the moment at
96 which we have to make a choice about which beta reduction to perform
97 next: one choice leads to a normal form, the other choice leads to
98 endless reduction:
99
100     let prefac = \f n. isZero n 1 (mult n (f (pred n))) in
101     let fac = Y prefac in
102     fac 2
103        = [(\f.(\x.f(xx))(\x.f(xx))) prefac] 2
104        = [(\x.prefac(xx))(\x.prefac(xx))] 2
105        = [prefac((\x.prefac(xx))(\x.prefac(xx)))] 2
106        = [prefac(prefac((\x.prefac(xx))(\x.prefac(xx))))] 2
107        = [(\f n. isZero n 1 (mult n (f (pred n))))
108           (prefac((\x.prefac(xx))(\x.prefac(xx))))] 2
109        = [\n. isZero n 1 (mult n ([prefac((\x.prefac(xx))(\x.prefac(xx)))] (pred n)))] 2
110        = isZero 2 1 (mult 2 ([prefac((\x.prefac(xx))(\x.prefac(xx)))] (pred 2)))
111        = mult 2 ([prefac((\x.prefac(xx))(\x.prefac(xx)))] 1)
112        ...
113        = mult 2 (mult 1 ([prefac((\x.prefac(xx))(\x.prefac(xx)))] 0))
114        = mult 2 (mult 1 (isZero 0 1 ([prefac((\x.prefac(xx))(\x.prefac(xx)))] (pred 0))))
115        = mult 2 (mult 1 1)
116        = mult 2 1
117        = 2
118
119 The crucial step is the third from the last.  We have our choice of
120 either evaluating the test `isZero 0 1 ...`, which evaluates to `1`,
121 or we can evaluate the `Y` pump, `(\x.prefac(xx))(\x.prefac(xx))`, to
122 produce another copy of `prefac`.  If we postpone evaluting the
123 `isZero` test, we'll pump out copy after copy of `prefac`, and never
124 realize that we've bottomed out in the recursion.  But if we adopt a
125 leftmost/call by name/normal order evaluation strategy, we'll always
126 start with the isZero predicate, and only produce a fresh copy of
127 `prefac` if we are forced to. 
128
129 Q.  You claimed that the Ackerman function couldn't be implemented
130 using our primitive recursion techniques (such as the techniques that
131 allow us to define addition and multiplication).  But you haven't
132 shown that it is possible to define the Ackerman function using full
133 recursion.
134
135 A. OK:
136   
137 <pre>
138 A(m,n) =
139     | when m == 0 -> n + 1
140     | else when n == 0 -> A(m-1,1)
141     | else -> A(m-1, A(m,n-1))
142
143 let A = Y (\A m n. isZero m (succ n) (isZero n (A (pred m) 1) (A (pred m) (A m (pred n))))) in
144 </pre>
145
146 For instance,
147
148     A 1 2
149     = A 0 (A 1 1)
150     = A 0 (A 0 (A 1 0))
151     = A 0 (A 0 (A 0 1))
152     = A 0 (A 0 2)
153     = A 0 3
154     = 4
155
156 A 1 x is to A 0 x as addition is to the successor function;
157 A 2 x is to A 1 x as multiplication is to addition;
158 A 3 x is to A 2 x as exponentiation is to multiplication---
159 so A 4 x is to A 3 x as super-exponentiation is to exponentiation...
160